Organizational commitment, technical quality and time in the team as antecedents to athlete’s centrality in sports team trust networks - Genoino, Ronan Kayano; Siqueira, João Paulo Lara (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
The study investigated what leads an actor to have greater centrality within trust networks of sports teams by verifying the relationship between centrality and organizational commitment, technical quality and time of team membership. The research was based on the concept of trust networks, a type of informal network that is formed by interpersonal trust relationships among the members of an organization. It had a qualitative, exploratory-descriptive nature and analyzed athletes of two sports teams. Data were collected by means of both questionnaires answered by the athletes and semi-structured interviews with the team coaches. The results indicated the existence of a positive relationship between the constructs, the main contribution being the parallel that can be made with the managerial field, in which more committed, qualified and experienced professionals within the organizations can enjoy greater confidence within the environment, which amounts to better organizational performance.